Synthesis and Characterization of Co(II), Ni(II), Cu(II), Zn(II) and Hg(II) Complexes of Bidentate Ligand of Schiff Base - Gurubasavaraj, P.M. (Asian Journal of Chemistry, 2016)
A few metallic complexes of Co(II), Ni(II), Cu(II), Zn(II) and Hg(II) metals with bidentate Schiff base have been prepared and characterized. The complexes were coloured, amorphous in nature and are soluble in DMSO and DMF. The conductance measurement shows the complexes are non-electrolytes in DMF. Elemental analysis confirmed to the 1 : 2 stoichiometry. Magnetic, electronic, IR and NMR spectral information suggest the squareplanar structure for Co(II), Ni(II) and Cu(II) complexes while tetrahedral geometry to Zn(II) and Hg(II) complexes.